Evaluates the Model Area Development Project for Quality-of-Life according to the New Theory Applied to the “Khok Nong Na Model” in the Ruan Kiang Na Center in Thailand - Chettha Muhamad, Daycho Khaenamkaew, Damrongphun Jaihoweweerapong, Pongprasit Onchan, Boonying Praphum, Peerapong Sutcharitpan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper evaluates the Model Area Development Project for Quality-of-Life according to the New Theory Applied to the “Khok Nong Na Model” in the Ruan Kiang Na Center in Thailand. The project is based on the concept of “Organic Farming” to continue the king’s philosophy in Na Mai Phai Sub-district, Thung Song District, Nakhon Si Thammarat province in Southern Thailand. The objective of the project was to assess the activities and improve the quality of life as per the new theory of organic farming in the “Khok Nong Na Model” in the Ruan Kiang Na Center in Na Mai Phai Sub-district in Southern Thailand. Organic Farming to Continue the King’s Philosophy in Na Mai Phai Sub-district, Thung Song District, Nakhon Si Thammarat Province. It consists of an assessment of the implementation of 4 activities in the CIPP model: environment, Inputs Process aspect, and productivity. The population of 17 householders who use the CIPP evaluation model was included in the study. The data were collected from the population and project area and analyzed using statistical variables: percentage, mean, tribute, and standard deviation. Evaluation of the data demonstrated that all four aspects of the model were at a high level (µ = 4.49, σ = 0.01) in the descending mean. The side with the highest mean was the yield at the highest level (µ = 4.59, σ = 0.49), followed by the environmental factors at the highest level (µ = 4.56, σ = 0.50. Very (µ = 4.47, σ = 0.50) and the side with the lowest mean is the process aspect was at a high level (µ = 4.34, σ = 0.48).